Różewicz: wiersze z ciemności - Próchniak, Paweł (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
The essay is an attempt to describe different varieties of "darkness" present in Różewicz's oeuvre and co-creating the imaginarium of his work. The author reproduces the internal network of complex relationships connecting the theme of dark with related motives and qualities. The darkness itself is understood here as a figure of the imagination, which with particular force reveals the existential dimension of Różewicz's poetry, but is also a trace of metaphysical recognition and is closely associated with the "secret", represented in the poet's works as "dark" reality, internally "disturbed", "cracked", full of "flaws", and yet in its own way "dead". In this context, the author of the essay addresses the dialogue of the poet with the Young Poland movement and includes the "dead" poetry of this period in the problem of the graveyard of poems characteristic of Różewicz, and thus the themes of "life" and "death" of poetry (and "living poetry"), so important to Różewicz, are linked with the "darkness" ("secret" and "death") as an analogue of experience – both poetic and existential.